1. Oblicz jak najprostszym sposobem :
a) 105 + (-7) + (-13) +20 =

b) -16 + 67 + (-10) + (-7) +66 =

c) 2 i 2/5 + (-4,1) + 7 i 3/5 + (-5,9) =

d) 4 i 4/7 + 5,4 + (-1 i 4/7) + (-7,4) =

e) -0,75 + 6,3 + (-1,1) + (-¼) + (-6,3) =

2. Oblicz :
a) 5 - 7 - 13 + 15 - 22=

b) -21 + 16 - 3 - 12 + 24=

c) 13,5 - 24 + 2,5 - 5,3 + 3,2 =

d) -3,6 + 2 i 3/7 - 1,4 - (-11/7) =

e) -2,75 + 4 i 2/3 - 2¼ - (-3 i 1/3) =

1

Odpowiedzi

2010-02-04T17:54:30+01:00
1. Oblicz jak najprostszym sposobem :
a) 105 + (-7) + (-13) +20 = 105 -20 + 20 = 105 [-7-13=-20]
b) -16 + 67 + (-10) + (-7) +66 = 66-16 +67-17=50+50=100
c) 2 i 2/5 + (-4,1) + 7 i 3/5 + (-5,9) =10-10=0 [2i2/5+7i3/5=10][-4,1-5,9=10]
d) 4 i 4/7 + 5,4 + (-1 i 4/7) + (-7,4) = 3-2=1 [4i4/7-1i4/7=3][5,4-7,4=-2]
e) -0,75 + 6,3 + (-1,1) + (-¼) + (-6,3) =-1,1-1=-2,2[-0,75-1/4=-1][6,3-6,3=0
2. Oblicz :
a) 5 - 7 - 13 + 15 - 22=20-20-22=-22
b) -21 + 16 - 3 - 12 + 24=-36+40=4
c) 13,5 - 24 + 2,5 - 5,3 + 3,2 =-24+15-2,1=-26,1+15=-11,1
d) -3,6 + 2 i 3/7 - 1,4 - (-11/7) = -3,6 + 2 i 3/7 - 1,4 +11/7=-5+4=-1 [2i3/7+11/7=4]
e) -2,75 + 4 i 2/3 - 2¼ - (-3 i 1/3) =-2,75 + 4 i 2/3 - 2¼ +3 i 1/3 =-5+8=3
48 4 48